Improving the Literacy Skills of Children in Kijang Jaya Village Through Competitions to Commemorate National Children's Day - Non Syafriafdi; Alwin Zein Nasution; Muhammad Irfan Ali; Parasian Sitorus; Rudi Hartono Simanjuntak; Dormauli Simanjuntak; Arauna Sipahutar; Cantika Khoiruroh; Yusnia Aprelia; Kharunia; Marsauli Simanullang (Indonesian Journal of Advanced Social Works, 2023)
KKN activities carried out by Riau University Students in Kijang Jaya Village carry several themes, one of which is literacy. The choice of theme was motivated by an analysis of the situation and conditions existing at the location where the KKN activities were carried out. This community service activity with a literacy theme aims to improve the literacy skills of children in Kijang Jaya Village. One of the programs included in the literacy theme is competition activities to commemorate National Children's Day on July 23 2023 at the Kijang Jaya Village Multipurpose Building. The competitions held were the Storytelling, Fast Accurate and Ranking 1 competitions. The competition implementation method consisted of two stages, namely the preparation stage and the implementation stage. The results obtained from this competition activity are an increase in children's knowledge and literacy skills.